Multiple binding sites in the nicotinic acetylcholine receptors: An opportunity for polypharmacolgy. (November 2015) - Iturriaga-Vásquez, Patricio; Alzate-Morales, Jans; Bermudez, Isabel; Varas, Rodrigo; Reyes-Parada, Miguel
Graphical abstract: Abstract: For decades, the development of selective compounds has been the main goal for chemists and biologists involved in drug discovery. However, diverse lines of evidence indicate that polypharmacological agents, i.e. those that act simultaneously at various protein targets, might show better profiles than selective ligands, regarding both efficacy and side effects. On the other hand, the availability of the crystal structure of different receptors allows a detailed analysis of the main interactions between drugs and receptors in a specific binding site. Neuronal nicotinic acetylcholine receptors (nAChRs) constitute a large and diverse family of ligand-gated ion channels (LGICs) that, as a product of its modulation, regulate neurotransmitter release, which in turns produce a global neuromodulation of the central nervous system. nAChRs are pentameric protein complexes in such a way that expression of compatible subunits can lead to various receptor assemblies or subtypes. The agonist binding site, located at the extracellular region, exhibits different properties depending on the subunits that conform the receptor. In the last years, it has been recognized that nAChRs could also contain one or more allosteric sites which could bind non-classical nicotinic ligands including several therapeutically useful drugs. The presence of multiple binding sites in nAChRs offers an interesting possibility for the development of novel polypharmacological agents with a wide spectrum of actions.